Performance Evaluation of a Microarchitecture With Multiple Flows of Control - Santos, Francisco; Santos, Rafael R.; Santos, Anna Dolejsi; C. Filho, Eliseu M.; Navaux, Philippe O. A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1999: Anais do XI Symposium on Computer Architecture and High Performance Computing, 1999)
This work presents a new approach to exploit the Instruction-Level Parallelism. In the MULFLUX microarchitecture each branch instruction spawns two different flows, corresponding to the two possible branch paths. Instructions from both flows are executed speculatively in parallel. Cycles consumed by discarded instructions are not visible, because the correct instructions also have been executed. The concept of multiple flows of control as exploited in this research work has provided promising results, with performance gains of up to 109% for a configuration supporting up to 16 aclive flows. Among the configurations considered here, the configuration with a maximum of 4 aclive flows exhibited the best compromise between performance and resource replication: it provided a performance gain of 105% and full dispatch width utilization of up to 41%.